Protein phylogeny gives a robust estimation for early divergences of eukaryotes: phylogenetic place of a mitochondria-lacking protozoan, Giardia lamblia. - Takuya Hashimoto; Yoshihiro Nakamura; Fuminori Nakamura; Tetsurou Shirakura; Jun Adachi; Naoko Goto; Ken‐ichi Okamoto; M. Hasegawa (1994)
A partial nucleotide sequence of the mRNA encoding a major part of elongation factor 1 alpha (EF1 alpha) from a mitochondria-lacking protozoan, Giardia lamblia, was reported, and the phylogenetic relationship among lower eukaryotes was inferred by the maximum-likelihood and maximum-parsimony methods of protein phylogeny. Both the methods consistently demonstrated that, G. lamblia among the four protozoan species being analyzed, is the earliest offshoot of the eukaryotic tree. Although the Giardia EF1 alpha gene showed an extremely high G+C content as compared with those of other protozoa, it was concentrated only at the third codon positions, resulting in no remarkable differences of amino acid frequencies vis-à-vis those of other species. This clearly suggests (a) that the amino acid frequencies of conservative proteins are free from the drastic bias of genome G+C content, which is a serious problem in the widely used tree of ribosomal RNA, and (b) that protein phylogeny gives a robust estimation for the early divergences in the evolution of eukaryotes.